THE ROLES OF COMMUNICATION SKILLS AMONG THE EMPLOYEES AT PT. PELINDO BELAWAN NORTH SUMATERA - Indah - Sari (Universitas Muhammadiyah Tapanuli Selatan, 2024)
In an increasingly competitive business environment, communication skills play an important role in determining the success of a company. This study aimed to analyze the role of communication skills in the corporate context and how this affects organizational performance. The study used qualitative method by administering open questionnaire to 30 respondents at PT. Pelindo Belawan North Sumatera. Data collected includes employees’ opinions of the importance of communication, the impact of communication skills on productivity and collaboration, as well as strategies for developing communication skills within the organization. The results showed that effective communication skills had a significant impact on company performance. Moreover, the practical implication of this study was the need for companies to prioritize the development of communication skills at all levels of the organization, through training, mentoring, and creating a conducive communication culture. In this way, companies can improve performance and competitiveness in a market that increasingly demands communication excellence.